The Viability of Applying Standards of Evaluation and School Excellence in the Secondary Schools for Girls in Makkah Al- Mukarramah; From the Principals and Teachers Perspectives - Alsobhi, Malak Abdorahman; Badaoud, Omar Mohammed Omar (Journal of Educational and Psychological Sciences, 2022)
This research study aims to identify the viability of applying standards of evaluation and school excellence in the secondary schools for girls in Makkah Al- Mukarramah from the principals and teachers’ perspectives. The researcher used the descriptive survey method, and a questionnaire as a research tool in which the questionnaires were distributed to the research sample that is consisted of (313) individuals, including (48) principals and (265) teachers, and (13%) out of the entire research community. The research found that the viability of applying standards of evaluation and school excellence in the secondary schools for girls in Makkah Al- Mukarramah resulted as (4.27 out of 5) overall average, i.e., with a (very high) degree of relevance. At the level of sub- domains, the School Leadership domain achieved (4.42) the highest average, then the domain of Learning Outcomes with an average of (4.28), then thirdly the domain of Teaching and Learning with an average of (4.23), of which all achieved a (very high) degree of relevance. The final domain is the School Environment that achieved an average of (4.04) and a (high) degree of relevance. The results showed that there are statistically significant differences between the responses of the research sample for the variable of (The Job) in favor of the school principals, and there are no differences for the variable of (Years of Experience). Differences were found for the domain of Learning Outcomes, in favor of those whose experience reached (10 years or more). Based on the results, the researcher recommended that there is a need to maintain this high level of quality, and to spread the culture of quality and school accreditation more in all schools at all educational levels in Makkah Al- Mukarramah and all secondary schools in Saudi Arabia.
Keywords: relevance; standards of evaluation; school accreditation; principals and teachers’ perspectives; secondary schools; Makkah Al- Mukarramah